Biomimetic Silica Particles with Self-Loading BMP-2 Knuckle Epitope Peptide and Its Delivery for Bone Regeneration - Mi-Ran Ki; Thi Khoa My Nguyen; Tae-In Park; Hae-Min Park; Seung Pil Pack (MDPI AG, 2023)
Biomimetic silica deposition is an in-situ immobilization method for bioactive molecules under biocompatible conditions. The osteoinductive P4 peptide derived from the knuckle epitope of bone morphogenetic protein (BMP), which binds to BMP receptor-II (BMPRII), has been newly found to contain silica formation ability. We found that the two lysine residues at the N-terminus of P4 played a vital role in silica deposition. The P4 peptide co-precipitated with silica during P4-mediated silicification, yielding P4/silica hybrid particles (P4@Si) with a high loading efficiency of 87%. P4 was released from P4@Si at a constant rate for over 250 h, representing a zero-order kinetic model. In flow cytometric analysis, P4@Si showed a 1.5-fold increase in the delivery capacity to MC3T3 E1 cells than the free form of P4. Furthermore, P4 was found anchored to hydroxyapatite (HA) through a hexa-glutamate tag, followed by P4-mediated silicification, yielding P4@Si coated HA. This suggested a superior osteoinductive potential compared to silica or P4 alone coated HA in the in vitro study. In conclusion, the co-delivery of the osteoinductive P4 peptide and silica by P4-mediated silica deposition is an efficient method for capturing and delivering its molecules and inducing synergistic osteogenesis.